2013
DOI: 10.1111/jopr.12025
|View full text |Cite
|
Sign up to set email alerts
|

The Quality of Removable Prostheses in Dentate, Community‐Dwelling Elderly Residing in Puerto Rico

Abstract: Purpose Edentulism has been decreasing in the US elderly population; however, due to the increasing number of elderly, the need for prostheses has been projected to rise over the next several decades. One of the aims of the Puerto Rican Elderly Dental Health Study (PREDHS) was to assess the quality of removable prostheses (RP) in the Puerto Rican (PR) elderly (> 69 years of age) population. Methods A cross-sectional design, using a subgroup from the Puerto Rican Elderly: Health Conditions (PREHCO) study of d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
1
0

Year Published

2015
2015
2015
2015

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 11 publications
0
1
0
Order By: Relevance
“…However, we are among the dental faculty members who recognize that not all students are adequately prepared in RPD design when they graduate. Clinical studies have also found a deficiency in the level of dental graduates’ technical knowledge about removable prostheses 2 , 3 . During the 2011 annual senior exit interviews, enough students at the University of Florida College of Dentistry stated they felt underprepared at graduation in RPD treatment to prompt faculty members to consider ways to improve students’ level of understanding and clinical performance.…”
mentioning
confidence: 99%
“…However, we are among the dental faculty members who recognize that not all students are adequately prepared in RPD design when they graduate. Clinical studies have also found a deficiency in the level of dental graduates’ technical knowledge about removable prostheses 2 , 3 . During the 2011 annual senior exit interviews, enough students at the University of Florida College of Dentistry stated they felt underprepared at graduation in RPD treatment to prompt faculty members to consider ways to improve students’ level of understanding and clinical performance.…”
mentioning
confidence: 99%